206k views
3 votes
-g+2(3+g)=-4(g+1)- Please help !

2 Answers

4 votes

Answer: G = -2

Step 1.

Subtract 6 from both sides.

g + 6 - 6 = -4g - 4 - 6

Step 2.

g = -4g - 10

Step 3.

Add 4g to both sides.

g + 4g = -4g - 10 + 4g

Step 4.

Simplify.

5g = -10

Step 5.

Divide both sides by 5.


(5g)/(5)=(-10)/(5)

Step 6.

Simplify.

1. Divide 5g by 5.


(5g)/(5)=g

2. Divide -10 by 5.


(-10)/(5)=-2

Hence, -2 is the answer.

User Tsewang
by
5.7k points
3 votes

Hey there! :)

-g + 2(3 + g) = -4(g + 1)

Simplify.

-g + 6 + 2g = -4g - 4

Add like terms.

(-g + 2g) + 6 = -4g - 4

Simplify.

g + 6 = -4g - 4

Add 4g to both sides & subtract 6 from both sides to isolate "g."

g + 4g + 6 - 6 = -4g + 4g - 4 - 6

Simplify.

5g = -10

Divide both sides by 5.

5g/5 = -10/5

Simplify.

g = -2

Hope this helped! :)

User Mkjh
by
5.3k points